Macroeconomic effects of Mobile money: Evidence from Uganda - Joseph Mawejje; Corti Eliab Paul Lakuma (Financial Innovation, 2019)
This study examined the effects of mobile money-a recent innovation in Uganda's financial-sector landscape-on aggregate economic activity and other macroeconomic variables. We first estimated the long-run mobile-money demand function using vector error correction (VEC) techniques, distinguishing between balances and transfers/transactions. We then estimated the short-run effects of mobile money on selected macroeconomic variables using structural vector autoregressive (SVAR) methods. The results showed that mobile money had moderate positive effects on monetary aggregates, consumer price index, private-sector credit, and aggregate economic activity. Mobile money balances responded to changes in monetary policy instruments, signaling possible ameliorating effects for the conduct of monetary policy. Finally, the results showed that transactional motives related to mobile money had stronger macroeconomic effects than savings motives.
Keywords: 650; Mobile money; Monetary policy; Inflation; Interest rates; Private-sector credit; Money demand; GDP; Uganda